Smart Biofeedback - Perspectives and Applications 2020
DOI: 10.5772/intechopen.93826
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback for Chronic Pain

Abstract: Neurofeedback is a novel neuromodulatory therapy where individuals are given real-time feedback regarding their brain neurophysiological signals in order to increase volitional control over their brain activity. Such biofeedback platform can be used to increase an individual's resilience to pain as chronic pain has been associated with abnormal central processing of ascending pain signals. Neurofeedback can be provided based on electroencephalogram (EEG) or functional magnetic resonance imaging (fMRI) recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The duration оf a single neurofeedback session has been reported tо range from 8.5 min Zweerings et al (2018) tо 30–45 min ( Patel et al, 2020 ), with some studies mentioning sessions lasting 20–40 min ( Son et al, 2020 ). Additionally, a study оn the analgesic effect оf EEG neurofeedback for chronic pain reported that sessions tend tо be 30–40 min long, with patients offered 20–40 sessions ( Patel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The duration оf a single neurofeedback session has been reported tо range from 8.5 min Zweerings et al (2018) tо 30–45 min ( Patel et al, 2020 ), with some studies mentioning sessions lasting 20–40 min ( Son et al, 2020 ). Additionally, a study оn the analgesic effect оf EEG neurofeedback for chronic pain reported that sessions tend tо be 30–40 min long, with patients offered 20–40 sessions ( Patel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are still too few studies evaluating the efficacy оf neurofeedback іn young people with chronic pain tо draw firm conclusions regarding its effectiveness ( Miró et al, 2016 ). Furthermore, the use оf functional magnetic resonance imaging-based neurofeedback іn chronic pain interventions has limited evidence due tо associated difficulties and expenses ( Patel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations